2021
DOI: 10.3390/ijerph18062953
|View full text |Cite
|
Sign up to set email alerts
|

A National Accessibility Audit of Primary Health Care Facilities in Brazil—Are People with Disabilities Being Denied Their Right to Health?

Abstract: Poor accessibility of healthcare facilities is a major barrier for people with disabilities when seeking care. Yet, accessibility is rarely routinely audited. This study reports findings from the first national assessment of the accessibility of primary health care facilities, undertaken in Brazil. A national accessibility audit was conducted by trained staff of all 38,812 primary healthcare facilities in Brazil in 2012, using a 22-item structured questionnaire. An overall accessibility score was created (22 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
2
16
0
1
Order By: Relevance
“…Just about a fifth of the PWDs in our study (19/91) were able to use facilities in public buildings by themselves, indicating a low level of independence. This level exhibits the reduced ability among PWDs towards accessing facilities independently in public buildings, which corresponds to reports of poor accessibility to these structures (Calder et al, 2018;Gladstone, 2015;Lontsi and Wandjie, 2022;Peterson, 2021;Pinto et al, 2021;Rimmer et al, 2017). Many PWDs may depend on others for help to overcome the resultant accessibility challenges, and this concurs with our related finding that most participants (79.1%) receive little or a lot of assistance to use such facilities.…”
Section: Level Of Independencesupporting
confidence: 88%
See 1 more Smart Citation
“…Just about a fifth of the PWDs in our study (19/91) were able to use facilities in public buildings by themselves, indicating a low level of independence. This level exhibits the reduced ability among PWDs towards accessing facilities independently in public buildings, which corresponds to reports of poor accessibility to these structures (Calder et al, 2018;Gladstone, 2015;Lontsi and Wandjie, 2022;Peterson, 2021;Pinto et al, 2021;Rimmer et al, 2017). Many PWDs may depend on others for help to overcome the resultant accessibility challenges, and this concurs with our related finding that most participants (79.1%) receive little or a lot of assistance to use such facilities.…”
Section: Level Of Independencesupporting
confidence: 88%
“…These statutes place deep emphasis on designing to facilitate PWDs’ level of independence towards using facilities to gain entry to, accomplish tasks, navigate areas and exit buildings on their own, as this demonstrates the measure of accessibility such users experience (National Disability Authority, 2023). However, diverse research on the design of public buildings mostly reveal poor levels of accessibility (Calder et al , 2018; Gladstone, 2015; Lontsi and Wandjie, 2022; Peterson, 2021; Pinto et al , 2021; Rimmer et al , 2017) and further portray the inclination to disregard accessibility issues in building practices (Rieger and Strichfaden, 2016) as regulatory controls are reported to be weak (Imrie and Kumar, 2010). These evidence primarily depict absent or reduced independent access to facilities by PWDs in such buildings, which falls short of the societal responsibility to ensure access for all (Carlsson et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a very recent work demonstrated that, the organization of accessibility and roads (OAR), as an important part of the community, contributes facilitating easier life of people with mobility disabilities and protecting their right to health from infringement (Pinto et al, 2021 ). Better OAR has more positive impact on people’s quality of life and well-being (Kingham et al, 2020 ).…”
Section: Conceptual Framework Literature Review and Hypothesesmentioning
confidence: 99%
“…As far as the study object is concerned, research on hospital accessibility can be roughly divided into four categories: (a) The supply and demand relationship of a specific hospital for a potential population with certain disease [20][21][22][23]; (b) measuring the spatial hospital accessibility for different groups combined social and economic indicators [24][25][26][27][28]; (c) modeling based on population size or facility level to assess and optimize the spatial distribution of medical facilities [29][30][31][32][33]; and (d) spatial comparison of hospital accessibility under different modes of transportation [34][35][36]. For example, Hare and Barcus explored the accessibility of Kentucky's heart-related hospital services by considering the bed-topopulation ratios jointly with the doctor-to-population ratios [20].…”
Section: Study On the Hospital Accessibilitymentioning
confidence: 99%